Effects of feeding frequency on the growth and production performance of indigenous catfish Clarias batrachus (Linnaeus, 1758) in ponds of Northern Bangladesh - Md. Selim Reza; Md. Abdus Samad; Jannatul Ferdous (Journal of Fisheries, 2021)
Effects of feeding frequency on the growth performance and production of Clarias batrachus was evaluated for a period of 180 days. Feeding frequency were once (T1), twice (T2) and thrice (T3) per day. Stocking density was 16750 fingerlings ha–1. The fish were initially fed 28% protein containing formulated feed at the rate of 8% of body weight which subsequently reduced to 5% at the end. The water quality parameters were monitored fortnightly and found similar across treatments and remained within the suitable ranges for aquaculture. The mean weight gain was 41.14±0.15, 44.49±0.78 and 56.10±0.86 g and specific growth rate (SGR) of 1.29±0.002, 1.33±0.01 and 1.44±0.01% per day in T1, T2 and T3 respectively. The highest survival rate was in T2 (96.23±0.76%) whereas the lowest was in T1 (95.32±0.76%). The lowest FCR (=best; 1.65±0.12) was found in T3 and the highest FCR (=worst; 2.14±0.15) was recorded in T1. The highest production was observed in T3 (3559.27±85.95 kg ha–1), which was significantly higher than that of other treatments. This study concludes that feeding three times per day is effective for C. batrachus.